A Narrative Review of the Legal, Jurisprudential and Ethical aspects of Embryo Donation: Implications for Infertility Counselling - Faezeh Ghorbani; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2022)
Background & aim: Embryo donation is one of the infertility treatment strategies that have various consequences. This review was carried out to investigate the legal, jurisprudential and ethical aspects of embryo donation with counseling approach in Iran.Methods: In this narrative review, the published evidence on various legal, jurisprudential and ethical aspects of embryo donation by Iranian authors was searched in English databases of PubMed, Scopus and CINAHL as well as the Persian databases of Iran Medex and SID. To collect data, keywords including "third party reproduction", "embryo donation", "infertility", "law", "jurisprudence", "ethics" and "Iran" were searched alone or in combination in English and their equivalent Persian words without time limitation. Out of 177 articles, 39 were included in the study.Results: The results showed that in the process of embryo donation, the legal dimensions of embryo donation such as lineage, inheritance, marriage, alimony, custody and citizenship should be considered in infertility counseling. Also the ethical dimensions of embryo donation i.e., informed consent, as well as screening donors and recipients, and its jurisprudential aspects including the juridical permission of the principle of embryo donation from the jurists' point of views are salient issues to be taken into account in recipient and donor counseling.Conclusion: It seems necessary to provide infertility counseling services based on the mentioned dimensions in embryo donation to recipient and donor couples.